Speaking Herbs: The Pragmatic Roles of Language in the Creation of Minak Pengalun in Karo Tradition - Karisma Erikson Tarigan (CV. Rustam, 2025)
This study examines the pragmatic functions of language and its interplay with non-verbal acts in the formulation and implementation of Minak Pengalun, a traditional herbal medicinal technique originating from the Karo culture of Indonesia. The study uses qualitative research methods, such as ethnographic fieldwork, interviews, and participant observations, to reveal how verbal expressions, gestures, and symbolic rituals coalesce to safeguard cultural heritage, convey ecological knowledge, and facilitate holistic healing. Employing Speech Act Theory, the study delineates five pragmatic functions of language in Minak Pengalun: representative acts communicate ecological and procedural knowledge, directive acts direct preparation and ritual execution, commissive acts signify practitioners' dedication to cultural authenticity, expressive acts demonstrate spiritual and emotional connections, and declarative acts affirm and reinforce cultural norms. The interplay between verbal communication and non-verbal rituals, including ingredient preparation and ritual gestures, guarantees the procedural precision and cultural congruence of the activity. The findings underscore Minak Pengalun as a comprehensive tradition in which language serves as a medium for meaning-making, connecting the spiritual, cultural, and ecological aspects of Karo identity. This research underscores the significance of safeguarding both linguistic and ceremonial elements of ancient traditions amidst cultural evaluation while also promoting additional comparative studies and techniques for intergenerational transmission. The study highlights the dynamic relationship between language and action and emphasizes the importance of Minak Pengalun in preserving cultural and natural legacy.